Treatment of bean seeds (Phaseolus vulgaris L.) with systemic insecticides for the management of Cerotoma arcuata (Olivier) (Coleoptera: Chrysomelidae) - da Silva, Igor Honorato Leduino; de Almeida, Waldiane Araújo; de Sousa, Adalberto Hipólito (EntomoBrasilis, 2020)
Bean (Phaseolus vulgaris L.) cultivation has great agricultural and food importance, but this crop production is generally affected by severe infestations of Cerotoma arcuata (Olivier) (Coleoptera: Chrysomelidae) in the northern region of Brazil. An alternative for leaf beetle control is the use of physiological insecticides acting in the initial phase of plant growth, through pre-sowing seed treatment. In this sense, this study aimed to evaluate the effects of systemic insecticides, based on thiamethoxam, imidacloprid and fipronil, on the germination performance of bean seeds, and to verify the efficacy of these insecticides on the control of C. arcuata. The research was carried out in two stages. Initially, under laboratory conditions, the influence of the insecticides on the germinating power of seeds was evaluated through the following parameters: germination, emergence, electrical conductivity and dry mass of the aerial part. In the field, the efficacy of the insecticides on the plant stand, number of insects per plant and level of foliar damage at 21 and 28 days of planting were evaluated. The insecticides investigated did not affect the germinating power of seeds when compared to the control. Regarding field results, there was a lower incidence of C. arcuata and less leaf damage to plants from seeds treated with systemic insecticides, showing greater crop protection in the period studied.